2002
DOI: 10.1016/s0002-9440(10)64443-4
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Regulation of CD97 in Colorectal Carcinoma Cell Lines and Tumor Tissues

Abstract: The expression of CD97, a member of the EGF-TM7 family with adhesive properties, is proportional to the aggressiveness and lymph node involvement in thyroid tumors. CD97 has never been systematically investigated in other tumors. First, we examined colorectal carcinoma cell lines (n ‫؍‬ 18) for CD97 expres-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
153
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 119 publications
(159 citation statements)
references
References 40 publications
4
153
2
Order By: Relevance
“…Na butyrate has been used as an inhibitor of proliferation in the MDA-MB-231 cells [50,51]. Na butyrate inhibits histone deacetylase, increases p21 expression, and decreases cyclin D gene expression [50] resulting in an arrest of the cell in G2 [51].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Na butyrate has been used as an inhibitor of proliferation in the MDA-MB-231 cells [50,51]. Na butyrate inhibits histone deacetylase, increases p21 expression, and decreases cyclin D gene expression [50] resulting in an arrest of the cell in G2 [51].…”
Section: Discussionmentioning
confidence: 99%
“…Na butyrate inhibits histone deacetylase, increases p21 expression, and decreases cyclin D gene expression [50] resulting in an arrest of the cell in G2 [51]. Na butyrate also induces cell differentiation [50], as shown with an increase in lipid accumulation, and a reduction in migration across multiple extracellular matrices [52].…”
Section: Discussionmentioning
confidence: 99%
“…CD97 levels correlate with the in vitro migration and invasion capacity of colorectal tumor cell lines and CD97-transfected cells. 6 Colorectal carcinomas with more strongly CD97-stained, scattered tumor cells at the invasion front showed a poorer clinical stage as well as increased lymph vessel invasion compared to cases with uniform CD97 staining. 6 In thyroid cancers, CD97 expression parallels the aggressiveness and lymph node involvement of these tumors.…”
mentioning
confidence: 88%
“…All leiomyomas and 9 out of 21 leiomyosarcomas were CD97 positive . The disability of muscular CD97 to bind the ligand CD55 implicates another function in this cell type (Wobus et al, 2004) as the suggested role as an adhesion molecule (Hamann et al, 1996) in tumor cells where CD97 promotes migration capacity (Galle et al, 2006;Steinert et al 2002). Based on these findings, we are eminently interested in CD97 regulatory mechanisms in SMCs.…”
Section: Introductionmentioning
confidence: 94%
“…We described CD97 expression in cells of the hematopoetic system and detected CD97 overexpression in tumor cells of different origin Steinert et al, 2002).…”
Section: Introductionmentioning
confidence: 99%